Antimicrobial and cytotoxic activity of Ocimum tenuiflorum and Stevia rebaudiana-mediated silver nanoparticles - An in vitro study - Indumathy Pandiyan; Meignana Indiran Arumugham; Sri Sakthi Doraikannan; Pradeep Kumar Rathinavelu; Jayashri Prabakar; S Rajeshkumar (Wolters Kluwer Medknow Publications, 2023)
Background: Silver nanoparticles (AgNPs) are the nanoparticles of silver between 1 nm and 100 nm in size. In this study, AgNPs were extracted from Ocimum tenuiflorum and Stevia rebaudiana which is a medicinal plant of Indian origin, worshipped by the Hindus and used in Ayurvedic medicine since ancient times. Aim: The aim of the study was to assess the antimicrobial and cytotoxic effect of AgNPs reinforced with the herb O. tenuiflorum and S. rebaudiana against oral pathogens. Materials and Methods: In this in vitro study, the organisms used were Streptococcus mutans, Staphylococcus aureus, Lactobacillus sp., and Candida albicans. Agar well-diffusion method was used to assess the antimicrobial efficacy of the nanoparticles at 25 μL, 50 μL, and 100 μL. To assess the cytotoxic effect, brine shrimp lethality assay was used. Results: Zone of inhibition was found to be highest at 100 μL against S. mutans, S. aureus, Lactobacillus sp., and C. albicans. The cytotoxic activity at 5 μL and 10 μL was 0%. The maximum cytotoxicity was seen at 80 μL where 30% of the Nauplii's died. Conclusion: The findings from this study suggest that AgNPs reinforced with O. tenuiflorum and S. rebaudiana extracts has the potential as an antimicrobial agent and has less cytotoxic effect on brime shrimp and can be used as an alternative to commercially available antimicrobial agents.